2022
DOI: 10.1111/jch.14547
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive emergencies in Asia: A brief review

Abstract: Hypertensive emergency is one of the most challenging conditions to treat in the emergency department (ED). From previous studies, about 1%–3% of hypertensive individuals experienced hypertensive emergencies. Its prevalence varied by country and region throughout Asia. Asian populations have more different biological and cultural backgrounds than Caucasians and even within Asian countries. However, there is a scarcity of research on clinical features, treatment, and outcomes in multinational Asian populations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Some differences are at least in part explained by the different HE/HU definitions, in terms of BP cut-off or diagnostic coding; in a large retrospective study, the prevalence of HE in the United States between 2006 and 2013 was lower, probably due to the strict definition, based on acute BP elevation together with a diagnosis of acute organ damage based on the ICD-9 code [ 2 ]. In a recent review, the prevalence of HE in the Asian population ranges from 0.1 to 1.5% [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some differences are at least in part explained by the different HE/HU definitions, in terms of BP cut-off or diagnostic coding; in a large retrospective study, the prevalence of HE in the United States between 2006 and 2013 was lower, probably due to the strict definition, based on acute BP elevation together with a diagnosis of acute organ damage based on the ICD-9 code [ 2 ]. In a recent review, the prevalence of HE in the Asian population ranges from 0.1 to 1.5% [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the persistence of arteriolar sclerosis can potentially lead to an increased incidence of arterial or vein occlusions within the eye [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…HTN-E is less common, with past studies reporting 0.2-0.8% of total ED evaluations [4,5]. A recent meta-analysis of ED evaluations across Europe, Southeast Asia, and South America found a similar rate of HTN-E, around 0.3% [6,7]. Despite the frequency of elevated BP in the ED meeting criteria, HTN-U is actually only diagnosed in 0.9% of ED discharges, either due to underdiagnosis or spontaneous improvement in ED [6,8].…”
Section: Epidemiologymentioning
confidence: 99%
“…Nitroprusside has been used to treat HTN-E with rapid onset and benefits of simultaneous preload and afterload reduction but has fallen out of favor secondary to cyanide toxicity. It also has the potential for increasing intracerebral edema in neurological emergencies [7]. One recent study found that nitroprusside was still favored by cardiologists over neurologists and emergency medicine physicians, secondary to these hemodynamic effects in the setting of LV dysfunction [26].…”
Section: Medication Selectionmentioning
confidence: 99%